2017
DOI: 10.3389/fnins.2017.00545
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Control of Visual Attention by the Prefrontal Cortex. Functional Specialization and Long-Range Interactions

Abstract: The ability to select information that is relevant to current behavioral goals is the hallmark of voluntary attention and an essential part of our cognition. Attention tasks are a prime example to study at the neuronal level, how task related information can be selectively processed in the brain while irrelevant information is filtered out. Whereas, numerous studies have focused on elucidating the mechanisms of visual attention at the single neuron and population level in the visual cortices, considerably less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 166 publications
(237 reference statements)
2
95
0
1
Order By: Relevance
“…Here we extend this literature by demonstrating retinotopic specificity beyond early visual areas in an absence of visual input, extending to parietal regions. Parietal regions and the frontal eye fields have been related to a top‐down modulatory control within a variety of cognitive tasks and imaging modalities [for review, please refer Paneri and Gregoriou (), Shomstein (), and Silver and Kastner ()]. In line with the fMRI literature, ventral, dorsal, and parietal cortices displayed specialized location tuning properties (Figure ).…”
Section: Discussionmentioning
confidence: 77%
“…Here we extend this literature by demonstrating retinotopic specificity beyond early visual areas in an absence of visual input, extending to parietal regions. Parietal regions and the frontal eye fields have been related to a top‐down modulatory control within a variety of cognitive tasks and imaging modalities [for review, please refer Paneri and Gregoriou (), Shomstein (), and Silver and Kastner ()]. In line with the fMRI literature, ventral, dorsal, and parietal cortices displayed specialized location tuning properties (Figure ).…”
Section: Discussionmentioning
confidence: 77%
“…Reviews of the functional specialization of PFC, specifically in the context of visual attention, have suggested that increased neural activity in the lateral PFC corresponds to target representations along with decreases during distractor representations, and that lesions of this area result in increased distractibility during cognitive performance (Chao & Knight, ; Lennert & Martinez‐Trujillo, ; Suzuki & Gottlieb, ; Gregoriou et al . ; Paneri & Gregoriou, ). These descriptions of lateral PFC involvement align nicely with our tDCS‐induced changes in the right lateral PFC's connectivity with posterior regions.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the lateral PFC may play an important role in the suppression of distracting information, while the ventral PFC acts as a reorienting system to salient stimuli (Corbetta & Shulman, ; Corbetta et al . ; Paneri & Gregoriou, ). Further, these regions appear to be intricately connected to posterior cortex including parietal regions and bottom‐up processors, with hierarchical organization of these networks implicating PFC specifically in top‐down control mechanisms (Miller, ; Brass et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While majority of classical studies have considered 'object recognition' as a feed-forward brain process (DiCarlo et al, 2012;VanRullen, 2012), recent studies have argued against this view by providing evidence on the significant influence of top-down task-dependent processes on bottom-up sensorydriven inputs (Harel et al, 2011;Bar et al, 2001;Bar et al, 2006;Vaziri-Pashkam and Xu, 2017). The effects of task are generally imposed on sensory processing by mechanisms generally referred to as prediction (Summerfield et al, 2006), expectation (Puri et al, 2009;Meijs et al, 2018;Manahova et al, 2018) and most importantly attention (Stokes et al, 2009;Spyropoulos et al, 2018;Rohenkohl and Nobre, 2011;Battistoni et al, 2017;Summerfield and Egner, 2009;Paneri and Gregoriou, 2017).…”
Section: Introductionmentioning
confidence: 99%